Genetic analysis reveals temporal population structure in Caribbean spiny lobster (Panulirus argus) within marine protected areas in Mexico - Truelove, N.; Ley-Cooper, K.; Segura-García, I.; Briones-Fourzán, P.; Lozano-Álvarez, E.; Phillips, Bruce; Box, S.; Preziosi, R. (Elsevier BV, 2015)
Management efforts for improving the sustainability of the Caribbean spiny lobster (Panulirus argus) fishery require knowledge of population connectivity. The aim of this study is to investigate population connectivity of P. argus at two levels: (1) spatially between two marine protected areas (MPAs) in the Caribbean coast of Mexico, and (2) temporally within MPAs; by genotyping discrete size classes lobsters using microsatellite markers. No evidence of population differentiation between lobster populations from Banco Chinchorro and Sian Ka'an MPAs was found (P=0.139). In contrast significant levels of population differentiation among discrete size classes of lobsters was found (FST=0.0054; P=0.0052). Temporal variation among the genotypes of new larval recruits may explain these results. Future research will be required to directly test the genotypes of new larval recruits in Banco Chinchorro and Sian Ka'an MPAs to confirm this hypothesis.